An Efficient Contourlet Based Multiple Watermarking Scheme For Health Information System - Munot, Mousami V; Turuk, Mousami P (International Journal of Computer Sciences and Engineering, 2025)
Health Information Systems (HIS) are gaining wide popularity in the recent days demanding digitization for easy storage of medical data in the secure environment that protects the patient privacy. As the medical data has been transferred on unsecure network authentication and integrity of medical data is a prime concern to attract the researchers. These objectives are gained by watermarking. Medical Image Watermarking (MIW) has recently evolved to solve the issues like storage, security and privacy related with HIS. This paper proposes an effective approach based on Contourlet Transform (CNT) for data hiding of medical records Electronic Patient Record (EPR), biographic signal like EEG or ECG and hospital logo. The contourlet transform is exploited in this research for its multiscale properties and predictive coding like ADM is proposed for compression of ECG signal. The medical text data is further encrypted using RSA public key algorithm. The efficacy of the developed approach is examined using various performance parameters ( Peak Signal to Noise Ratio, PSNR and Structural Similarity Measure , SSIM).The Quality of extracted logo and recovered ECG is evaluated using Normalized Correlation Coefficient (NC) .The similarity of original and extracted EPR examined using Bit Error Rate (BER).Imperceptibility of algorithm is preserved as PSNR values are above 45 DB And MSSIM is greater than 0.98.The comparative analysis with other frequency domain techniques is presented which claims and confirms the superiority of proposed contourlet approach for efficient multiple watermarking in HIS.